2016
DOI: 10.1176/appi.ajp.2015.15010124
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Postpartum Relapse in Bipolar Disorder and Postpartum Psychosis: A Systematic Review and Meta-Analysis

Abstract: One-third of women at high risk experience a postpartum relapse. In women with bipolar disorder, continuation of prophylactic medication during pregnancy appears highly protective for maintaining mood stability postpartum. In women with a history of isolated postpartum psychosis, initiation of prophylaxis immediately after delivery offers the opportunity to minimize the risk of relapse while avoiding in utero medication exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
4
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(270 citation statements)
references
References 52 publications
(79 reference statements)
9
232
4
6
Order By: Relevance
“…The postpartum period is a time of elevated risk for recurrence, with 66% of women who were medication free during pregnancy and 23% of those on treatment experiencing a mood episode following the delivery 534. The risk of postpartum relapse is highest in women who also experienced a mood episode during pregnancy and those who are not on prophylactic treatment 535.…”
Section: Specific Populationsmentioning
confidence: 99%
“…The postpartum period is a time of elevated risk for recurrence, with 66% of women who were medication free during pregnancy and 23% of those on treatment experiencing a mood episode following the delivery 534. The risk of postpartum relapse is highest in women who also experienced a mood episode during pregnancy and those who are not on prophylactic treatment 535.…”
Section: Specific Populationsmentioning
confidence: 99%
“…A recent meta-analysis of studies reporting on postpartum recurrences found that the rates varied widely; for bipolar disorder between 9 and 75%; and for puerperal psychosis between 14 and 57% (Wesseloo et al, 2016). This may well reflect differences in definitions of recurrence, the range of phenotypes being included and, importantly, whether women were or were not on medication.…”
Section: Risks Related To Bipolar Disordermentioning
confidence: 99%
“…Almost one in five (17%) new mothers with BD are admitted for psychiatric treatment in the early postpartum (Wesseloo et al, 2016), a period in which the risk of admission is significantly greater for these women than at any other time in their lives (Munk-Olsen et al, 2009). Relative to the general population, the risk of postpartum psychosis (PP) is dramatically elevated in women with BD, increasing from one in a thousand to approximately one in five deliveries (Di Florio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%